2004
DOI: 10.1007/s00011-004-0360-7
|View full text |Cite
|
Sign up to set email alerts
|

Computerized visualization of quality of life data of individual cancer patients ? the QoL-Profiler

Abstract: Practitioners found QoL-profiles comprehensible and clinically useful. QoL profiles are the crucial link between the QoL concept and QoL enhancing treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Another study by Middeke et al found that all the participating physicians reported the QOL profiles were easy to understand and clinically relevant, and more than half of the physicians indicated the profiles had provided them with additional information that led to a more complete diagnosis [78]. …”
Section: Resultsmentioning
confidence: 99%
“…Another study by Middeke et al found that all the participating physicians reported the QOL profiles were easy to understand and clinically relevant, and more than half of the physicians indicated the profiles had provided them with additional information that led to a more complete diagnosis [78]. …”
Section: Resultsmentioning
confidence: 99%
“…Additional suggestions have been to map QOL outcomes to standardized toxicity grading and to allow patients to check which aspects of QOL they would like to discuss with clinical staff (Velikova et al , 2008). To this end, several automated systems for assessing QOL have been developed by researchers for clinical use (Middeke et al , 2004; Velikova et al , 1999; http://www.nihpromis.org/default.aspx), which could easily be adapted to transplant settings. An additional option is Internet‐based assessment, in which patients can complete the QOL measures over the Internet, either from home or in the waiting room (Basch et al , 2005; Jones et al , 2007; Snyder et al , 2009).…”
Section: Qol In Caregivers Of Hct Patientsmentioning
confidence: 99%
“…Lober, Berry, Wolpin, & Rae, 2005; Karras et al, 2006;. Middeke, Bauhofer, Kopp, & Koller, 2004; Taenzer et al, 1997). Technology-enhanced assessment has gained acceptance as an alternative method of self-reporting symptoms and QOL issues in lieu of paper forms because of its comprehensiveness, time savings, and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the acceptability of computer-based programs in oncology settings have reported moderate to high level of acceptance among patients (Basch et al, 2007; Mullen et al, 2004). Most investigators described acceptability and usability of computer programs using various types of exit interview questionnaires, with no report on the reliability of the instruments used (Basch et al, 2005, 2007; Bush et al, 2005; Middeke et al, 2004; Taenzer et al, 1997. ).…”
Section: Discussionmentioning
confidence: 99%